Interest, boredom, and stress as determinants of motivation to learn in physical education - Andik Setiawan; Miftakhul Jannah; Abdul Rachman Syam Tuasikal; Fatih Hazar; Nicola Lovecchio (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
Student motivation in Physical Education (PE) remains a challenge, as low participation and engagement in physical activities highlight the role of psychological factors such as interest, boredom, and stress. This study aims to analyze the effects of these factors on students' learning motivation in PE. A quantitative approach with a causal-associative design was applied to 157 10th and 11th-grade students at Dharma Mulya Christian High School in Surabaya using saturation sampling. Data were collected using a Likert-scale questionnaire covering four variables: interest (15 items), boredom (6 items), stress (15 items), and learning motivation (14 items), all of which met validity and reliability criteria. Data were analyzed using multiple linear regression, classical assumption tests, the coefficient of determination (R²), and hypothesis testing (F-test and t-test). The results showed that interest, boredom, and stress simultaneously had a significant effect on learning motivation (F = 33.612 > 2.66; α = 0.05), with an Adjusted R² of 0.396. Partially, interest had a positive effect, boredom had a negative effect, and stress showed a conditional influence on learning motivation. These findings confirm that interest functions as an intrinsic driver of motivation, while boredom and stress act as psychological factors that influence student engagement. Practically, the findings suggest the need for structured, varied, and activity-based learning strategies to enhance participation, reduce boredom, and minimize learning-related stress in Physical Education.